Prices, distribution and investment in Italy 1951-1966: an interpretation - SYLOS LABINI, P. (PSL Quarterly Review, 2014)
The work analyses the Italian economy from 1951 to 1966. The first part of the paper is devoted to the theoretical hypotheses which find their place in a model of the Italian economy illustrated in the second part. The author is mainly concerned with clarifying certain theoretical points and, in particular, initiating a type of analysis which considers variations in certain important aggregates and in certain categories of prices and wages simultaneously, which helps to bridge macro- and micro-economics. JEL: E31, E24